2020
DOI: 10.1007/s11340-020-00639-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Strain-Rate Behavior of a Viscoelastic Gel Under High-Velocity Microparticle Impact

Abstract: Background: Impact experiments, routinely performed at the macroscale, have long been used to study mechanical properties of materials. Microscale high-velocity impact, relevant to applications such as ballistic drug delivery has remained largely unexplored at the level of a single impact event. Objective: In this work, we study the mechanical behavior of polymer gels subjected to high-velocity microparticle impact, with strain rates up to 10 7 s -1 , through direct visualization of the impact dynamics. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Recent experiments by Veysset et al allowed the development of a refined model for particle impact in yield-stress fluids at intermediate Reynolds number (Fig. 10d) (141). In all gels tested, it was shown that, under micro-scale testing, the resistance to penetration, related to materials strength, significantly increased compared to macroscale experiments by orders of magnitude, evidencing rate strengthening effects.…”
Section: A Target Response 1 Dynamic Hardness Of Bulk Materialsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent experiments by Veysset et al allowed the development of a refined model for particle impact in yield-stress fluids at intermediate Reynolds number (Fig. 10d) (141). In all gels tested, it was shown that, under micro-scale testing, the resistance to penetration, related to materials strength, significantly increased compared to macroscale experiments by orders of magnitude, evidencing rate strengthening effects.…”
Section: A Target Response 1 Dynamic Hardness Of Bulk Materialsmentioning
confidence: 87%
“…Other soft materials beyond polymers, such as gels or biomaterials, have also been tested with LIPIT to determine their rate-dependent properties. Notably gelatin and synthetic gels, including poly(styrene-bethylene-co-butylene-b-ethylene) (SEBS) polymer-based gels with non-aqueous solvent, with varying concentrations were investigated (140,141). Particle trajectories were observed in the transparent specimen (Fig.…”
Section: A Target Response 1 Dynamic Hardness Of Bulk Materialsmentioning
confidence: 99%
“…The Poncelet model was previously applied to LIPIT studies to predict the penetration depth, δ t , into thick polymer gels. 22 However, we are interested in a slightly different problem: the conditions of the impact test and the materials properties that determine the onset of complete penetration through a film of finite dimensions.…”
Section: Connecting Different Energy Scalesmentioning
confidence: 99%
“…To address this challenge, significant effort in recent years has gone towards developing new characterization techniques capable of extracting information on the high strain-rate mechanical behavior of soft materials -including small-scale ballistic cavitation, 18 laser-induced particle impact testing, 19 shear impact testing, 20 and Inertial Microcavitation Rheometry (IMR), [21][22][23][24][25] which is the focus of the present work. IMR belongs to a class of cavitation-based material characterization techniques 26 -including needle-induced cavitation 11,12,18 and volume-controlled cavity expansion [13][14][15] -and is unique in its ability to mechanically characterize soft materials at high strain rates greater than 10 3 s À1 .…”
Section: Introductionmentioning
confidence: 99%